ON SOME DERIVATIVE MEANS OF NEGATIVE FORMS OF THE VERB IN UZBEK AND ENGLISH (Scientific journal of the Fergana State University, 2026)
This article examines the methods of forming the negative form of verbs through the use of the -ma affix in Uzbek, a productive grammatical feature, and the English negative particle not. These markers, commonly used in everyday speech, convey various negative and contextual meanings and are applied differently depending on the context. Their usage is analyzed through examples taken from literary texts to illustrate the semantic and grammatical patterns of negation in both languages.